Discovering Voices: College Students and Middle Schoolers Explore Identities, Differences, and Connections through the Structure of a Poem - Cook-Sather, Alison; Kenealy, Anne; Rippel, Maurice; Beyer, Julia (International Journal of Multicultural Education, 2018)
Co-authored by a college professor, a middle-school teacher, a college undergraduate, and a 7th grader, this article focuses on college and middle-school students’ experiences of discovering their own and others’ voices. The discovery unfolds through composing and reflecting on poems in the form of Jacqueline Woodson’s “it’ll be scary sometimes,” which focuses on the experience of being different. The students’ dis-covering of voices deepens their own and their teachers’ education and creates spaces, structures, and processes that affirm students’ diverse histories and identities. Honoring differences and finding connections in these ways contribute to greater equity and inclusiveness.